2013
DOI: 10.1111/j.1476-5381.2012.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for cardiovascular disease: the demise of alchemy and rise of pharmacology

Abstract: Regenerative medicine holds great promise as a way of addressing the limitations of current treatments of ischaemic disease. In preclinical models, transplantation of different types of stem cells or progenitor cells results in improved recovery from ischaemia. Furthermore, experimental studies indicate that cell therapy influences a spectrum of processes, including neovascularization and cardiomyogenesis as well as inflammation, apoptosis and interstitial fibrosis. Thus, distinct strategies might be required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 215 publications
(242 reference statements)
0
19
0
Order By: Relevance
“…HGF inhibits vascular permeability and pro-inflammatory effects [19,20]. Bicistronic plasmids coding VEGF with HGF seems to be effective during the first stage of the neoangiogenesis gene therapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…HGF inhibits vascular permeability and pro-inflammatory effects [19,20]. Bicistronic plasmids coding VEGF with HGF seems to be effective during the first stage of the neoangiogenesis gene therapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in regenerating damaged myocardial tissue has led to explore the application of stem cells therapy. A number of stem cell types have been investigated as possible sources for regenerating damaged myocardium: resident cardiac stem cells (CSC), embryonic stem cells (ESC), induced pluripotent stem cells (iPSC), adult bone marrow-derived (BM) cells, mesenchymal cells, endothelial progenitor cells umbilical cord blood (UCB) cells (Laflamme and Murry, 2011, Kumar et al, 2010, Segers and Lee, 2008, Shah and Shali, 2009, Kucia et al, 2004Jadczyk et al, 2013, Jameel and Zhang, 2010. CSCs are naturally residing within the myocardium.…”
Section: Heart -Biological Backgroundmentioning
confidence: 99%
“…Transplantation of proangiogenic cells following an acute myocardial infarction (MI) may help prevent the infarct extension by promoting cardiomyocyte rescue, awakening the hibernated myocardium in the area at risk, and modulating inflammation and fibrosis 2, 3. Cell therapy of coronary artery disease has evolved rapidly from bench to bedside; however, despite positive results in murine models of MI, small‐ or medium‐sized clinical studies and meta‐analyses have only shown modest benefit in humans 4, 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%